A Journey Through Development of Inland Waterways in India - Gupta, Aditya; Anand, Neeraj; Bansal, A K (Archives of Business Research, 2017)
Inland Waterways (IWT) is the finest mode of transportation available.With lowest capital cost, low running cost and low maintenance cost the cost of moving goods through this mode is just a fraction of other modes like Road and Rail.On top of this IWT is an environment friendly mode with least external costs.India has been blessed with long navigable waterways in excess of 14000 KM.However, post-independence IWT never got the desired attention resulting in IWT share of total transportation a meagre 0.4%.This prompted the authors to evaluate the progress of IWT since independence, the various challenges being faced and suggest possible steps to increase IWT share in India. The paper outlines the various waterways in India, the governance structure to manage IWT, various policies and programs undertaken by Indian authorities to promote IWT, a comparison of Indian IWT with US, China and EU, the key barriers in growth and future recommendations.